Impact of anticoagulation therapy on short-term and long-term prognosis of patients with acute Q-wave myocardial infarction after thrombolytic therapy - Kyselov, S. M. (Zaporozhye Medical Journal, 2018)
Prognosis in acute Q-wave myocardial infarction is an actual problem till nowadays. Aim: to determine the different regimens of anticoagulation therapy impact on hospital and one-year mortality, acute postinfarction aneurysm and left ventricle thrombus formation in patients with acute Q-wave myocardial infarction after thrombolytic therapy. Materials and methods: hospital and one-year mortality, risk of postinfarction aneurysm and left ventricle thrombus formation were investigated in 167 patients with acute Q-wave myocardial infarction after thrombolytic period depending on anticoagulation therapy. Probability of unfavorable cardiovascular events was assessed by the relative risk with a confidence interval of 95 %. The multiple method of Kaplan-Meier estimation was used to determine the survival distributions. In order to compare survival in different groups the Log-rank test was used. For all types of analyses differences were significant if P < 0.05. Results. It was found that survival during the hospital period was significantly higher in the group of patients received unfractionated heparin compared to patients received fondaparinux. Treatment with unfractionated heparin in comparison with fondaparinux, reliably reduces the relative risk of death during the hospital period. There were no significant differences in the one-year survival of patients who received fondaparinux, enoxaparin, and unfractionated heparin. Thus, all three approaches were equally effective for the long-term prognosis in patients with Q-wave myocardial infarction. There were no significant differences when comparing the relative risk of aneurysm formation and left ventricular aneurysm with a thrombus in the groups of patients with Q-wave myocardial infarction and different anticoagulation therapy. Thus, aneurysm of the left ventricle and left ventricular aneurysm with a thrombus occurred with the same frequency in patients with Q-wave myocardial infarction who were treated with low-molecular or unfractionated heparin. Conclusions. The usage of unfractionated heparin in patients with acute Q-wave myocardial infarction after thrombolytic therapy significantly reduces the risk of hospital mortality by 1.46 times compared with low-molecular-weight heparin. As for one-year mortality, the risk of acute aneurysm and left ventricular aneurysm with a thrombus, the unfractionated and low-molecular-weight heparin were equally effective.